The factor structure of the physical condition of the 13 year-old young men going in orienteering - Галан, Ярослав; Іванчук, Марія; Кушнір, Ірина; Сваричевська, Анжела; Koshura, Andrey; Baidiuk, Mykola; Ярмак, Олена (Editura Universitatea din Pitesti, 2019)
The article presents the results of the study that lasted during the 2017-2018 academic year. The study involved 132 young men aged 13 years (n=132) from the city of Chernivtsi. The purpose of the research was to identify the leading factors of the physical condition of 13-year-old young men who are orienteering at the initial preparation stage. To achieve this goal, the following research methods were used in this work: theoretical analysis and synthesis of scientific literature data; anthropometric research methods; physiological methods; psychological methods; methods for assessing physical performance; pedagogical methods; statistical data processing methods. The article presents the factor structure of the physical condition of 13-year-old youths goingin orienteering. The percentage contribution of each factor was determined, and it was found that the overall physical condition is determined by a group of four factors: the cardio-respiratory system - the largest contribution - 28.4 %, cognitive functions - 25.3 %, physical fitness and performance, and coordination abilities have a contribution of 22.1 %, physical development has a contribution of 8.6 %, which together make up 84.4 % of the variance explained. We found that the most factor loadings have indicators that characterize: endurance, running 1,000 m race (r = -0.868 with p <0.01); cognitive functions, information processing speed (r = -0.850 with p <0.01), short-term memory capacity (r = 0.848 with p <0.01), volume of the processed information (r = 0.834 with p <0.01); total body size, body weight (r = -0.845 with p <0.01), as well as indicators characterizing the fat component: the amount of skin fat folds (r = 0.829 with p <0.01). The results of the research have prognostic significance for the individualization and differentiation of the training process, as well as assessing the impact of the main means and methods at the initial preparation stage of 13-year-old young men in orienteering.
Keywords: factor structure; physical condition; young men; orienteering; Факторна структура; фізичний стан; юнаки; орієнтування